2005
DOI: 10.1074/jbc.m505562200
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Non-productive Conformations Underpins Rapid Electron Transfer to Electron-transferring Flavoprotein

Abstract: Crystal structures of protein complexes with electrontransferring flavoprotein (ETF) have revealed a dual protein-protein interface with one region serving as anchor while the ETF FAD domain samples available space within the complex. We show that mutation of the conserved Glu-165␤ in human ETF leads to drastically modulated rates of interprotein electron transfer with both medium chain acyl-CoA dehydrogenase and dimethylglycine dehydrogenase. The crystal structure of free E165␤A ETF is essentially identical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(64 citation statements)
references
References 26 publications
4
60
0
Order By: Relevance
“…Different Etf Af -Bcd Af contact areas were tested, but no orientation was found that meets the 14 Å distance criteria for an appropriate electron transfer rate between ␣-FAD and Dh-FAD (42). Therefore, we suggest a reorientation of domain II analogous to that observed between human Etf in the isolated and in complex with MCAD (43). The distance between the two FAD can thus be shortened to about 10 Å.…”
Section: ) (5)mentioning
confidence: 99%
See 1 more Smart Citation
“…Different Etf Af -Bcd Af contact areas were tested, but no orientation was found that meets the 14 Å distance criteria for an appropriate electron transfer rate between ␣-FAD and Dh-FAD (42). Therefore, we suggest a reorientation of domain II analogous to that observed between human Etf in the isolated and in complex with MCAD (43). The distance between the two FAD can thus be shortened to about 10 Å.…”
Section: ) (5)mentioning
confidence: 99%
“…These conformational changes are realistic because of the soft solvent-mediated domain II-(I ϩ III) interface and their realization in the related Etf-MCAD and Etf-TMADH systems (36,41). It might be triggered by productive NADH binding conveyed to domain II and/or by Bcd binding (43).…”
Section: ) (5)mentioning
confidence: 99%
“…Reduction of the flavin upon substrate binding is expected to affect this π-π interaction. It has been implied in the MACD:ETF co-crystal structure study that the indole of this residue plays an undefined role in electron transfer between ACADs and ETF [24, 27]. However, a role in the mechanism of electron transfer seems dispensable since replacing IVD Trp166 with a Phe residue did not abolish transfer of electrons to ETF.…”
Section: Discussionmentioning
confidence: 99%
“…The co-crystallization of human medium chain acyl-CoA dehydrogenase (MCAD) with human ETF, has provided additional evidence for the ability of ETF to bind its ACAD partners in the absence of their acyl-CoA substrates [23]. Important insight into the molecular mechanism of electron transfer in the oxidative half-reaction has also been gained with the crystallization of MCAD and the ETF βE165A complex [24]. …”
mentioning
confidence: 99%
“…More recently we have obtained the production in Escherichia coli and purification of rat Me 2 GlyDH as a recombinant active holoenzyme [27], thus providing the basis for further characterization of this enzyme, through kinetic, site-directed mutagenesis and structural studies. Indeed, the recombinant Me 2 GlyDH holoenzyme has been used as a redox partner of human electron-transferring flavoprotein in interprotein electron transfer studies [28].…”
Section: Introductionmentioning
confidence: 99%